Peningkatan Keterampilan Menceritakan Kembali Isi Cerpen Dengan Strategi Think Talk Write - Sulastri Sulastri (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This study aims to improve the skill of retelling the contents of short stories for students of class IX.6 of SMP Negeri 12 Pekanbaru by using Think Talk Write learning strategies. This type of research is classroom action research. The research subjects were students of class IX.6 consisting of 40 students. The object of this research is storytelling skills. Data collection techniques used in this study include questionnaires, observations, interviews, field notes, and storytelling skills tests. The results of this study indicate that the implementation of the Think Talk Write strategy can improve the storytelling skills of students in class IX.6 of SMP Negeri 12 Pekanbaru. The improvement was shown from the quality of the learning process which was reflected in the activeness, attention and concentration of students in the lessons, students' interest during learning, the courage of students to tell stories in front of the class. Product improvement can be seen from the class average score obtained from the pre-action stage to cycle II. In the pre-action stage the average grade score obtained at 16.84 increased to 21.42 in the first cycle stage. It increased again to 28.31 in the second cycle. Keyword: storytelling skills, Think Talk Write Abstrak: Penelitian ini bertujuan untuk meningkatkan keterampilan menceritakan kembali isi cerpen siswa kelas IX.6 SMP Negeri 12 Pekanbaru dengan menggunakan strategi pembelajaran Think Talk Write. Jenis penelitian ini adalah penelitian tindakan kelas. Subjek penelitian adalah siswa kelas IX.6 yang terdiri atas 40 siswa. Objek penelitian ini adalah keterampilan bercerita. Teknik pengumpulan data yang digunakan dalam penelitian ini meliputi, angket, observasi, wawancara, catatan lapangan, dan tes keterampilan bercerita. Hasil penelitian ini menunjukkan bahwa penerapan strategi Think Talk Write dapat meningkatkan keterampilan bercerita siswa kelas IX.6 SMP Negeri 12 Pekanbaru. Peningkatan tersebut ditunjukkan dari kualitas proses pembelajaran yang tercermin dari keaktifan, perhatian dan konsentrasi siswa pada pelajaran, minat siswa selama pembelajaran, keberanian siswa bercerita di depan kelas. Peningkatan secara produk dapat dilihat dari skor rata-rata kelas yang diperoleh dari tahap pratindakan sampai siklus II. Pada tahap pratindakan skor rata-rata kelas yang diperoleh sebesar 16,84 meningkat menjadi sebesar 21,42 pada tahap siklus I. Meningkat lagi menjadi 28,31 pada siklus II. Kata kunci: keterampilan bercerita, Think Talk Write